Formulated Pellet Feed from Cabbage Waste and Fish Meal for Local Catfish (Clarias batrachus) - Yuansah, Afrika; Listiana, Ika; Supriyadi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2025)
Cabbage waste is household and market industry waste that contains significant nutrients, such as protein, fat, fiber, vitamins, and minerals. This waste has the potential to be utilized as animal feed, for example, for local catfish (Clarias batrachus). This study aims to utilize cabbage waste as an alternative feed. The research was conducted from April to June 2024 using a quantitative experimental method and proximate analysis on the feed, with four treatments, three replications, and a positive control. The results showed that treatment 3, with a feed dosage of 12%, was the most effective in influencing all observed parameters. This treatment resulted in a length growth of 14.22 cm, weight growth of 20.59 g, and a feed conversion ratio (FCR) of 1.73, which was better than the other treatments. The proximate analysis results indicated that the feed in treatment 3 contained 32.14% protein, 5.24% fat, and 9.30% carbohydrates.